Authority, Hierarchy and the Commune. A Textual Analysis of Öcalan And Bookchin In Light of The Pkk Dissolution Process - Grasso, Davide (PARTECIPAZIONE E CONFLITTO, 2025)
This article analyses the texts published by Öcalan between February and June 2025. It does so by focusing on some excerpts from the Perspektif sent to the PKK 12th Congress and published in Serxwebûn. A comparative textual analysis relates its content to that of some antecedent works by Öcalan and Murray Bookchin. The analysis seeks to achieve two objectives: (a) to show how the contrast between the commune and the state, central to the Perspektif, is reflected in the earlier elaboration, by Öcalan and Bookchin, of the relational phenomenology of communalist and domineering relations; and (b) to show how the ambivalence that the concepts of authority and hierarchy retain in both authors can help to frame and better understand Öcalan's comprehension of the authority he claims over the party. The analysis will focus on two core components of the Perspektif's argument: (a) the need for a turning point in the self-critical transformation of the personalities of the party cadres; (b) the need to base this transformation on a thorough understanding of the dilemma of choosing between commune and state. The analysis will show that the understanding of state authority and of the related mentality, as set out in Öcalan's Manifesto and Prison writings, revolves around logical and phenomenological antecedents to the state such as domination, authority, and hierarchy. While dominating attitudes, in his view, ought to be marginalised in the post-PKK transformed personalities, authority and hierarchy seem to maintain implicit practical relevance due to an ambivalence that they retain in societies organised around communal forms of cooperation.